2010
DOI: 10.5424/sjar/2010083-1269
|View full text |Cite
|
Sign up to set email alerts
|

Forage yield and quality of intercropped corn and soybean in narrow strips

Abstract: Maize-soybean intercropping can increase forage quality with no detrimental effect on dry matter (DM) yield. The objective of this study was to compare corn-soybean intercrop in narrow strips with corn as monocrop in terms of DM yield and forage quality. This study was conducted in Matamoros, Coahuila (Mexico) in 2006 and 2007. Intercrops were established in rows spaced 0.50 m apart, evaluating alternate corn-soybean strips with one, two, three, and four rows per crop, and a treatment using an alternate twin-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
4
17
1
Order By: Relevance
“…For most of the arrangements, soybean contributed with more than 10% of the total biomass, although, treatments 1M+1S-30, 2M+1S-30 and 1M+1S-45 showed lower values (Table 5). Results resemble those reported by Sánchez et al (2010) in a two-year study. Note.…”
Section: Bromatological Traits Of Maize+soybean Silagesupporting
confidence: 89%
See 2 more Smart Citations
“…For most of the arrangements, soybean contributed with more than 10% of the total biomass, although, treatments 1M+1S-30, 2M+1S-30 and 1M+1S-45 showed lower values (Table 5). Results resemble those reported by Sánchez et al (2010) in a two-year study. Note.…”
Section: Bromatological Traits Of Maize+soybean Silagesupporting
confidence: 89%
“…Batista et al (2017) evaluating maize + soybean intercrop (1M+1S) reported similar biomass yield among intercrop and maize monocrop. Sánchez et al (2010) reported that maize plants at border rows showed higher dry mass biomass, which turns out in similar yield of maize monocrop.…”
Section: Crops Silage Biomass Dry Mass and Biomass Yieldmentioning
confidence: 75%
See 1 more Smart Citation
“…The starch concentration decreased and the NDF concentration increased or remained unchanged by intercropping. Javanmard et al [17] and Sánchez et al [37] also reported increased levels of crude protein but a decreased level of NDF in mixed silage of maize and other legumes such as soybean (G. max), vetch (Vicia villosa), bitter vetch (Vicia ervilia), berseem clover (Trifolium alexandrinum) and common bean (Phaseolus vulgaris) compared with sole maize silage. Higher dry matter Different superscript letters within columns indicate significant differences (p \ 0.05) between the treatments (a and b for the main effect of treatment, e and f for the main effect of location and v, x, y and z for the interaction treatment 9 location) digestibility in silage of intercropped maize and faba bean compared with sole maize has been found previously in a sheep digestion trial [32], as confirmed by the results of the present study.…”
Section: Forage Qualitymentioning
confidence: 99%
“…Different crop combination ratio affects forage yields ( Kumar et al, 2003;Chen et al, 2004) and crude protein (CP) yield (Altin, 1982). In addition, results showed that CP yields per hectare increased with corn-legume intercrop than that of monocropped corn (Javanmard et al, 2009;Sánchez et al, 2010;Baghdadi et al, 2014). The proportion of seed of intercropping components is one of factor that affects forage yield and CP content.…”
Section: Introductionmentioning
confidence: 99%